Patch antenna above an absorbing ground - Xie, Shijie (Nanyang Technological University, 2020)
In radio technology, an antenna is the interface between radio waves spreading through space and electric flows moving in metal conveyors, utilised with a transmitter or receiver. In transmission, a radio transmitter provides an electric current flow to the terminals of antenna, and the antenna emanates the power from the current as radio waves. In receiver, an antenna captures a portion of the intensity of an electromagnetic wave so as to deliver an electric current at its terminals. Antennas are fundamental components of all radio hardware. An antenna is an arrangement of conductors, electrically associated with the transmitter or receiver. Antennas can be designed to server different purpose such as directional, or high-gain, or “beam” antennas which in specific direction. Omnidirectional antennas are transmitting and receiving radio waves in all horizontal directions equally. In this research, our goal is to design a patch antenna above an absorbing ground with Absorptive Frequency Selective Reflector (AFSR). With the simulation through software ANSYS HFSS, the performances for this new 3D structure can be displayed clearly and directly.